Right Ventricular Dysfunction is related with Poor Exercise Tolerance in Elderly Patients with Heart Failure with Preserved Ejection Fraction - Chiara Fossati; Valentino D'Antoni; Jeganath Murugesan; Deborah Fortuna; Serena Selli; Noemi Punzo; Giuseppe Caminiti (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2017)
Background: Exercise intolerance (EI) is a cardinal feature in subjects with heart failure with preserved ejection fraction (HFpEF). Factors related to EI in such patients are not completely understood. The association between right ventricular (RV) dysfunction and pulmonary hypertension (PH) with EI has been poorly investigated so far. We hypothesized that RV function measured by Tricuspid Annular Plane Systolic Excursion (TAPSE)/Pulmonary Arterial Systolic Pressure (PASP) ratio would predict EI assessed by 6-Minute Walking test (6MWT) in elderly patients with HFpEF.  Methods: this was a retrospective study in which data of one hundred twenty-six patients with HF and left ventricular ejection fraction >50%, were collected. All subjects underwent an echocardiographic evaluation and a 6MWT. Results: Overall 43 out of 126 (34.1%) patients had RV dysfunction according to TAPSE value. TAPSE (r=0.28 p=0.042) and PASP (r=-0.33 p=0.028) were both significantly related to 6MWT distance. In a multivariate regression analysis PASP (adjusted OR = 1.39; 95% CI=1.18-1.66, p= 0.044) and TAPSE (adjusted OR = 1.43; 95% CI=1.22-2.65, p= 0.013) resulted independently related to EI. The median value of TAPSE/PASP ratio was 0.46. TAPSE/PASP ratio was significantly related to the 6MWT distance (r=0.48; p=0.007). Patients with TAPSE/PASP ratio<0.46 had larger RV diastolic diameter, higher NYHA class and were more likely to have atrial fibrillation and be treated with diuretics.